Respuesta al crecimiento vegetativo de cinco especies maderables aplicando abonos vegetales – Moyobamba - Ruiz Inuma, Wilmar Jefferson (2014)
The existing forest species in the Peruvian Amazon, in most cases it is possible its spread through seeds, cuttings, branches or natural regeneration; however sorne species the percentage of getting the seeds is low, or almost void; this situation, it is still a problem when work is being carried out reforestation, planting trees, usually when one wants to use species which have these difficulties. That is why it is necessary and very important research work on the production of forest plants in vivarium, through the sexual and asexual propagation by setting up systems and indexes of reproduction between species. Silviculturalmente the major percentage of mortality in the production of plants in forest nurseries, gives itself sexual way, which proves being a problem of deficiency in the supply of plants to the big plantations,which stimulates start production systems asexual in nurseries, where this research will be the production of plants by means of cuttings, where there will be evaluations on the basis of the response to the vegetative growth of five timber species using the plant fertilizers, in forest species that have difficulty in the supply of seeds for propagation in addition to being endemic species and that are difficult to obtain seed and to establish this propagation system it will allow to establish systems of rapid and guaranteed reforestation. Key words: planting trees, vivarium.